2005
DOI: 10.2337/diabetes.54.3.811
|View full text |Cite
|
Sign up to set email alerts
|

Pioglitazone Induces Vascular Smooth Muscle Cell Apoptosis Through a Peroxisome Proliferator-Activated Receptor-γ, Transforming Growth Factor-β1, and a Smad2-Dependent Mechanism

Abstract: Thiazolidinediones, such as pioglitazone, seem to exert direct antiatherosclerotic and antirestenotic effects on type 2 diabetes, in part due to an induction of vascular smooth muscle cell (VSMC) apoptosis. We aimed to study the role of transforming growth factor (TGF)-␤ in rat aortic VSMC. Pioglitazone at 100 mol/l increased apoptosis without affecting DNA synthesis, and this effect was reversed by an anti-TGF-␤1 antibody. Extracellular TGF-␤1 levels were rapidly increased after treatment with pioglitazone in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
50
3

Year Published

2005
2005
2016
2016

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 68 publications
(55 citation statements)
references
References 20 publications
2
50
3
Order By: Relevance
“…The canonical pathway of TGF-␤1 in VSMC involves activation of ALK-4/ 5/7 receptor-related kinases, which phosphorylates Smad2 (Ten Dijke et al, 2002). Interestingly, the importance of the TGF-␤1/Smad2 pathway in PIO-mediated rat VSMC apoptosis has been demonstrated by our group (Redondo et al, 2005). We found that PIO increased TGF-␤1 release in rat VSMC and that this cytokine mediated the apoptosis of PIO through the Smad2 pathway.…”
supporting
confidence: 52%
See 1 more Smart Citation
“…The canonical pathway of TGF-␤1 in VSMC involves activation of ALK-4/ 5/7 receptor-related kinases, which phosphorylates Smad2 (Ten Dijke et al, 2002). Interestingly, the importance of the TGF-␤1/Smad2 pathway in PIO-mediated rat VSMC apoptosis has been demonstrated by our group (Redondo et al, 2005). We found that PIO increased TGF-␤1 release in rat VSMC and that this cytokine mediated the apoptosis of PIO through the Smad2 pathway.…”
supporting
confidence: 52%
“…Because TGF-␤1 seems to be involved in the apoptotic effect of PIO, we studied whether this drug was able to increase the release of TGF-␤1 from cultured human VSMC obtained from nondiabetic and diabetic patients pretreated with 15 mM glucose for 48 h before PIO treatment. Figure 4A shows a rapid and transient increase in the release of total TGF-␤1 induced by 100 M pioglitazone as early as 30 min after treatment in VSMC from nondiabetic patients, as reported in rat VSMC (Redondo et al, 2005). However, VSMC from diabetic patients showed a different pattern of TGF-␤1 release.…”
Section: Apoptotic Effect Of Pioglitazone On Human Vascularmentioning
confidence: 64%
“…Pioglitazone increases transforming growth factor ␤1 secretion and phosphorylation of Smad2 in cultured VSMCs. 77,78 PPAR-␥ agonists increase IRF-1 gene expression while inducing VSMC apoptosis, and conversely inhibition of IRF-1 by antisense oligonucleotide decreases the VSMC apoptosis in vitro. 79 However, VSMC apoptosis can decrease the stability of atherosclerotic plaques and predispose them to rupture.…”
Section: Ppar-␥ Activation/inactivation In Vsmcsmentioning
confidence: 99%
“…[75][76][77][78][79] The mechanisms include upregulation of growth arrest and DNA damageinducible gene 45 expression, 75,76 as well as p53 expression (Figure 2). 76 The transforming growth factor ␤1/Smad2 pathway 77,78 and IFN regulatory factor (IRF)-1 79 are also involved ( Figure 2). Pioglitazone increases transforming growth factor ␤1 secretion and phosphorylation of Smad2 in cultured VSMCs.…”
Section: Ppar-␥ Activation/inactivation In Vsmcsmentioning
confidence: 99%
“…22,23 Furthermore, the TGF-β1-Smad2 pathway is involved in apoptosis of vascular smooth muscle cells induced by pioglitazone, a peroxisome proliferatoractivated receptor γ ligand. 24 TGF-β is also known to inhibit endothelial cell proliferation via the ALK5-Smad2/3 pathway, [25][26][27] whereas inhibition of ALK5 facilitates endothelial cell proliferation. 26,27 We also investigated whether ALK5 inhibitor can induce regression of cavernous fibrosis.…”
Section: Discussionmentioning
confidence: 99%